Effects of pronoun brand name perspective and positioning on brand attitude. Issue 2 (20th April 2015) - Kachersky, Luke; Carnevale, Marina
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the relative effectiveness of the second-person pronoun perspective within a brand name (as in "You"Tube) and the first-person pronoun perspective (as in "i"Phone). Design/methodology/approach – Drawing on prior research on self-concept, general pronoun usage and the fit between branding tactics and positioning, it is predicted that "you" will garner more favorable consumer responses when the brand is positioned on social benefits, while "I" will garner more favorable responses when the brand is positioned on personal benefits. These predictions are tested in two experiments with US consumers. Findings – When the brand in the experiment was positioned for its social benefits, "you" elicited more favorable brand attitudes than "I", while the opposite was true when the brand was positioned for its personal benefits. This effect tends to be stronger among those with higher self-esteem. Practical implications – Managers can make more informed pronoun brand name selections based on their brand's intended positioning – if it is social, "you" should be used; if it is personal, "I" should be used. Originality/value – The influence of pronouns in brand names is still largely unexplored. This research is the first to examine "you" brand names and also sheds light on how another marketing variable – positioning – impacts consumer preference for pronoun brand names. Finally, this work shows that such effects are more pronounced for those with higher self-esteem.